Exploring global changes in nitrogen and phosphorus cycles in agriculture induced by livestock production over the 1900-2050 period - Bouwman, L.; Goldewijk, Kees Klein; Hoek, K.W. Van Der; Beusen, A.H.W.; Vuuren, Detlef P. van; Willems, J.; Rufino, Mariana C.; Stehfest, Elke (National Academy of Sciences, 2013)
Crop-livestock production systems are the largest cause of human alteration of the global nitrogen (N) and phosphorus (P) cycles. Our comprehensive spatially explicit inventory of N and P budgets in livestock and crop production systems shows that in the beginning of the 20th century, nutrient budgets were either balanced or surpluses were small; between 1900 and 1950, global soil N surplus almost doubled to 36 trillion grams (Tg)•y−1 and P surplus increased by a factor of 8 to 2 Tg•y−1. Between 1950 and 2000, the global surplus increased to 138 Tg•y−1 of N and 11 Tg•y−1 of P. Most surplus N is an environmental loss; surplus P is lost by runoff or accumulates as residual soil P. The International Assessment of Agricultural Knowledge, Science, and Technology for Development scenario portrays a world with a further increasing global crop (+82% for 2000–2050) and livestock production (+115%); despite rapidly increasing recovery in crop (+35% N recovery and +6% P recovery) and livestock (+35% N and P recovery) production, global nutrient surpluses continue to increase (+23% N and +54% P), and in this period, surpluses also increase in Africa (+49% N and +236% P) and Latin America (+75% N and +120% P). Alternative management of livestock production systems shows that combinations of intensification, better integration of animal manure in crop production, and matching N and P supply to livestock requirements can effectively reduce nutrient flows. A shift in human diets, with poultry or pork replacing beef, can reduce nutrient flows in countries with intensive ruminant production.